Book review: Beker, Victor A. (2021): Preventing the Next Financial Crisis, Routledge, Abingdon, UK and New York, NY, USA (172 pages, hardcover, ISBN 978-0-367-48398-2) - Guillermo J. Escudé (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2021)
The pervading climate of financial innovation coupled with stagnant regulation of the 1990s and early 2000s led to one of the greatest financial crises on record: the 2007–2009 US financial meltdown, which quickly propagated to other financial centers and initiated what has been called the Great Recession. Between 2007 and 2009 a great many national economies experienced recession. Many issues were involved in the run-up to this highly complex phenomenon. Victor Beker's book has the virtue of analysing each of these issues in the light of the sizable amount of research undertaken before, during, and especially after the crisis.
Keywords: 330